Paneer Whey-Apricot Wine: Effect of bentonite treatment and aging and comparative sensory evaluation - Jindal, Harsh; Panjagari, Narender Raju; Ganguly, Sangita (Indian Journal of Dairy Science, 2026)
This study explored the impact of varying bentonite concentrations and aging on the physico-chemical properties and comparative sensory analysis of paneer whey-apricot wine (PWAW) with whey wine (WW), apricot wine (AW) and a commercial apricot wine (MAW). Wine namely WW (without apricot) and AW (without whey) were considered as control samples. The results revealed that the light transmittance of PWAW treated with 1% bentonite was significantly higher (89.75%) compared to the untreated samples (80.81%) (p